GERAKAN JUMAT BERSIH DESA LENGKONG SEBAGAI WUJUD NYATA PENDIDIKAN LINGKUNGAN HIDUP - Alifah Nur Habibah; Bintang Kleo La Neni; Fajar Fajriansyah; Fuji Rahmawati; Ridho Juliano; Siti Fatimah; Rita Kusumah (STKIP Subang, 2026)
This study examines the implementation of the Friday Clean Movement (Jumsi) in Lengkong Village as a concrete manifestation of community-based environmental education. The background of this research is the increasing problem of environmental cleanliness in rural areas that requires a collective and sustainable solution. The purpose of this study is to describe the implementation of Jumsi, identify its impact on community environmental awareness, and find the supporting and inhibiting factors of the activity. This qualitative case study involved 12 informants through participatory observation, in-depth interviews, and document analysis. Data were analyzed using the Miles, Huberman, and Saldana model. Results show that: (1) Jumsi is carried out every Friday morning involving all elements of the Lengkong Village community; (2) the program significantly increased residents' ecological awareness; (3) the main supporting factors are strong village leadership and the spirit of mutual cooperation; (4) inhibiting factors include limited facilities and uneven participation. This study concludes that Jumsi is an effective non-formal environmental education model that can be replicated in other villages.